One novel deletion and one splicing mutation of the LKB1 gene in two Chinese patients with Peutz-Jeghers syndrome - Chen, Chunyan; Zhang, Xiaomei; Wang, Fangyu; Liu, Chang; Lu, Heng; Wan, Haijun; Wei, Juan; Liu, Jiong (DNA and cell biology, 2012)
Peutz-Jeghers syndrome (PJS) is an uncommon autosomal dominant inherited disease, characterized by the occurrence of gastrointestinal hamartomatous polyps and pigmentation of the lips, buccal mucosa, and digits. Patients with PJS have a significant risk for developing tumors in multiple organs. Germline mutation of the LKB1 gene, which encodes a serine/threonine kinase that acts as a tumor suppressor, has been identified as a cause of PJS. The current study included two Chinese PJS probands and their available family members, as well as 200 unrelated healthy controls for comparison. Genomic DNA was extracted from the peripheral blood of these subjects. The nine coding exons and flanking introns of the LKB1 gene in the two probands and their family members were amplified by polymerase chain reaction (PCR) and then directly sequenced. Mutations identified in the patients were checked in the 200 healthy controls by PCR and denaturing high-performance liquid chromatography. Total RNA was extracted from the patient who was found to have a dubious splice site mutation and his available family members. Reverse transcription PCR was performed to identify the abnormal splicing caused by the splice site mutation. Two types of mutations were detected in the two PJS families. One type was a previously unreported 30-base-pair deletion in exon 4, and the other was an intron mutation that affected splicing. None of the 200 controls had either of these two types of mutations. The results provide support that mutation of the LKB1 gene is a cause of PJS, and expand the spectrum of LKB1 gene mutations.